The effect of CTL approach based on NHT learning model toward studentsâ motivation, science cchievement, and retention - Fausan, Muhammad Mifta; Pujiastuti, Indah Panca (Jurnal Pendidikan Biologi Indonesia, 2017)
The learning is an interaction process between students and their environment in order to improve good behavior. The results of observation which has been done in grade V SDN No. 4 Tanjung Batu showed that the studentsâ motivation and science achievement were low. This was becaused by the learning process which was still product oriented (based on material content), consequently, this lead to limit the learning is merely on memorizing concept activities. One of the learning approach that can be used to solve this problem is the Contextual Teaching and Learning (CTL) based on Numbered Head Together (NHT). This research aims to determine the effect of CTL based on NHT toward studentâs motivation, science achievement, and retention. Subjects in this research were the students of grade V SDN No. 4 Tanjung Batu. This research is a quasi-experimental using post-test only control design. The data obtained were analyzed by using descriptive and inferential statistical analysis. The research instruments were observation sheets and written test. The results showed that there was significant effect of CTL based on NHT toward studentsâ motivation, science achievement, and retention. It can be seen from the independent sample t-test results which showed significant value less than 0.05.